Clinical outcomes and 30-day mortality following significant upper gastrointestinal bleeding in users of anti-platelet agents and non-steroidal anti-inflammatory drugs. (13th March 2011) - Taha, A S; McCloskey, C; Craigen, T; Angerson, W
Abstract : Introduction: The use of antiplatelet agents for vascular protection continues to increase and this has been associated with serious complications including upper gastrointestinal bleeding (UGIB). The clinical outcomes following such complication remains poorly understood. We, therefore, aimed to measure 30-day mortality and other clinical outcomes in patients presenting with UGIB while using antiplatelet agents as compared with those using non-steroidal anti-inflammatory drugs (NSAIDs) and those using neither of these agents. Methods: Patients were included in the analysis if they presented with haematemesis and/ or melaena and had an endoscopic abnormality to explain their UGIB. Patients were excluded if they were well enough not to require hospital admission or if they had oesophageal or gastric varices. The Charlson and the complete Rockall scores were used to measure comorbidity and assess UGIB, respectively. Death of any cause within 30 days of UGIB was recorded. Drug therapy was noted including NSAIDs and antiplatelet drugs (low-dose aspirin, clopidogrel, dipyridamole and warfarin). The χ 2 test for categorical variables and Kruskal-Wallis test for continuous variables were used. Results: 990 patients entered the analysis. Their characteristics and outcomes are shown in table 1 . Conclusion: Patients with UGIB and taking antiplatelet drugs, with or without NSAIDs, stay longer in hospital, are more likely to require transfusion and to die within 30 days after UGIB. They are also older and have higher comorbidity and Rockall scores than bleeders not taking NSAIDs or anti-platelet agents.